Rational Design and Characterization of Transdermal Patch of Irbesartan for Hypertension - Dubey, Roshan Kumar; Dewangan, Hitesh Kumar (Indian Journal of Pharmaceutical Education and Research, 2020)
Background: Irbesartan is hypertensive drugs approved for high blood pressure and protect the kidneys damage due to diabetes. It is an angiotensin receptor blockers, belongs to BCS class II, exhibit low and variable oral bioavailability due to its poor aqueous solubility. Therefore, it is need to enhancement of dissolution rate and bioavailability. The objective of this study was to develop a transdermal patches system of Irbesartan to reduce the above drawback. Methods: Various batch of Irbesartan loaded transdermal patches were prepared by the solvent extraction method employing HPMC and ethyl cellulose as polymer in presence or absence of eudragit. Physicochemical characterization of patches was done by thickness, weight variation, folding endurance, drug content, moisture uptake and loss. The drug interaction was carried out by FTIR spectroscopy. Further, patches were evaluated their in-vitro drug release, ex-vivo permeation study in Franz diffusion cell. While in-vivo skin irritation and toxicity study performed in Wistar rats. Results: The final batch was selected on the basis of physicochemical characteristics and proceeds for further studies FTIR result indicates that there is no interaction between drug and polymer. The in-vitro release study showed that 93.54% of drugs released at 48 hr and steady-state flux was found to be 0.35±3.23 μg/cm2/h. the developed patch were free from edema and hypersensitivity reaction which is confirm by in-vivo study. Conclusion: Patches were successfully prepared and their evaluation of excellent quality and uniformity. This can be the potential for therapeutic application due to reduced dosing frequency, improve patient compliance and bioavailability.
Keywords: Irbesartan; Transdermal patch; Polymer; Formulation; Hypertension; Therapeutic